1985
DOI: 10.1111/j.1748-1716.1985.tb07767.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcitonin on elemental distribution and ultrastructure of rat submandibular gland acinar cells

Abstract: The effect of calcitonin on rat submandibular gland acinar cells was investigated by X-ray microanalysis and electron microscopy. Calcitonin caused a transient increase of the cellular calcium and magnesium concentration, but did not affect the intracellular concentration of other electrolytes. The relative volume of intracellular mucus increased from 45% in control glands to 72% at 6 h after administration of calcitonin. Calcitonin caused an inhibition of the cellular response of the acinar cells to beta-adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…T h e CT-induced increase in total cellular calcium levels in submandibular acinar cells (Sagulin et al 1985) is not in contradiction with the present findings that CT does not affect 1987). affect the calcium/protein ratio in the final saliva.…”
Section: Measurements Of [Ca'+]contrasting
confidence: 60%
See 3 more Smart Citations
“…T h e CT-induced increase in total cellular calcium levels in submandibular acinar cells (Sagulin et al 1985) is not in contradiction with the present findings that CT does not affect 1987). affect the calcium/protein ratio in the final saliva.…”
Section: Measurements Of [Ca'+]contrasting
confidence: 60%
“…In a previous study we found that C T causes accumulation of mucus in rat submandibular acinar cells (Sagulin et al 1985). It appears reasonable to suggest that the inhibition of cAMP production in the glands by C T would be at least partly responsible for the observed inhibition of mucus secretion.…”
Section: Measurements Of [Ca'+]mentioning
confidence: 89%
See 2 more Smart Citations
“…Since the concentration of calcium in the mucus granules is much higher thar in any other cell compartment, the cellular calcium concentration sr 9b mandibular acinar cells is largely determined by the relative volume of intracellular mucus (Roomans, 1986). Accumulation of intracellular mucus is also seen after treatment wit reserpine, and after chronic treatment with isoproterenol and other beta adrenergic agonists (Muller and Roomans, 1985), and with furosemide (Scarlett et at, 1988), and caln he induced by a single dose of alloxan (Sagsrrom et 19a,197) and calcilonin (Sagulin et at, 1985). In general, mucu:s accumulation appears to be associated with a reduced response to beta: adrenergic stimulation of low to moderate intensity, but the molecular basis of this reduction may be different for the var ious treatments.…”
Section: Discussionmentioning
confidence: 95%